Perivascular Arrest of CD8+ T Cells Is a Signature of Experimental Cerebral Malaria. - Tovah N Shaw; Phillip J Stewart-Hutchinson; Patrick Strangward; Durga B Dandamudi; Jonathan A Coles; Ana Villegas-Mendez; Julio Gallego-Delgado; Nico van Rooijen; Egor Zindy; Ana Rodriguez; James M Brewer; Kevin N Couper; et al. (PLoS Pathogens)
There is significant evidence that brain-infiltrating CD8+ T cells play a central role in the development of experimental cerebral malaria (ECM) during Plasmodium berghei ANKA infection of C57BL/6 mice. However, the mechanisms through which they mediate their pathogenic activity during malaria infection remain poorly understood. Utilizing intravital two-photon microscopy combined with detailed ex vivo flow cytometric analysis, we show that brain-infiltrating T cells accumulate within the perivascular spaces of brains of mice infected with both ECM-inducing (P. berghei ANKA) and non-inducing (P. berghei NK65) infections. However, perivascular T cells displayed an arrested behavior specifically during P. berghei ANKA infection, despite the brain-accumulating CD8+ T cells exhibiting comparable activation phenotypes during both infections. We observed T cells forming long-term cognate interactions with CX3CR1-bearing antigen presenting cells within the brains during P. berghei ANKA infection, but abrogation of this interaction by targeted depletion of the APC cells failed to prevent ECM development. Pathogenic CD8+ T cells were found to colocalize with rare apoptotic cells expressing CD31, a marker of endothelial cells, within the brain during ECM. However, cellular apoptosis was a rare event and did not result in loss of cerebral vasculature or correspond with the extensive disruption to its integrity observed during ECM. In summary, our data show that the arrest of T cells in the perivascular compartments of the brain is a unique signature of ECM-inducing malaria infection and implies an important role for this event in the development of the ECM-syndrome.